Optimization of Parameters for Alkali Pretreatment on Coir Fiber for Biomass Production Using TOPSIS. - Sushma Verma; Vinay Kumar Midha; Awadesh Kumar Choudhary (Journal of Natural Fibers, 2022)
Coir is a lignocellulosic fiber which is quite preferable in the production of biofuels and chemicals. Conversion of cellulose and hemicellulose to biofuels requires five main unit processes out of which, pretreatment plays a major role because all subsequent processes depend upon the pretreatment results. Partial degradation of lignin, hemicellulose, and breakdown of the sugars also occur during the pretreatment of the coir. So, the optimal condition selection is vital. In this paper, an attempt has been made to optimize the parameters (time, NaOH concentration, and temperature) by Box-Behnken design in order to get the optimum level of lignin, hemicellulose, and cellulose. To obtain an ideal solution, the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is used to rank the optimized solutions. Further, to find the authenticity of TOPSIS, the top three ranked solutions are again tested. It is observed that error percentage increases with an increase in rank order.